Improving Theoretical Fundamentals of Physical Culture Classes - Abdullaev Jasurbek Xolmirzaevich (Zien Journals, 2022)
This article discusses the theory of physical education, physical maturity, physical training and physical development of preschool children, the fact that physical culture is part of the general culture, a set of material and spiritual wealth of society in the field of human physical development accumulated in the course of socio-historical practice. 'z goes
Keywords: physical culture, theory of physical education, physical maturity, physical training, physical development.